Functionalized Carbonaceous Materials as Cathode for Lithium-Ion Batteries. Issue 45 (13th June 2016) - Zhong, Hai; Wang, Chunhua; Xu, Zhibin; Ding, Fei; Liu, Xingjiang
ABSTRACT: Activated carbon materials are integrated into functionalization of graphene nano-sheets to serve as a high-power lithium cathode. The electrochemical performance shows that the composite displays the highest reversible capacity ( c . 170 mAh g -1 ) comparing with functionalized graphene and activated carbon. Also, approximately 92% of its capacity can be retained after 4, 000 cycles at a current of 1 A g -1 . Moreover, the composite exhibits an excellent rate performance, a reversible capacity of 90 mAh g -1 even at 6 A g -1, which corresponds to the power density of 15.2 kW kg -1 and energy density of 227 Wh kg -1, respectively. The high performance of this composite can be attributed to the fact that the activated carbon particles not only reduce the graphene sheet stacking thus making it easier for ions to diffuse, but also act as an ion storage buffer against accelerating electron transfer.